The Effectiveness of Mindful Learning-Based Restitution Strategies “Berani Pidato” (Berapi) to Improve Speech Writing Skills - Bhayu Anggita Subarkah; Eko Suroso (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2025)
The abstract (in english) should concisely summarize the following: (1) brief background (if necessary); (2) aim and/or scope of the study; (3) brief description of the methodology used; (4) summary of the findings; and (5) conclusion. The abstract must be written in English in a single paragraph containing 150–250 words, without references, footnotes, or citations. Use Arial 11, single-spaced, and italicized font.  This study aims to analyze the effectiveness of implementing the Mindful Learning-based BERAPI (Berani Pidato) Strategy in improving the speech writing skills of eighth-grade students at SMP Negeri 2 Kroya in 2025. The research used a quantitative approach with a quasi-experimental design through a nonequivalent control group design. The research subjects included all 256 eighth-grade students, with a sample of 64 students who had initial scores ranging from 60 to 70. The sample was divided into two groups, namely the experimental group and the control group, each consisting of 32 students. Data collection was conducted through a speech writing test assessed using a speech writing skill assessment rubric that had undergone validity and reliability testing. Data analysis was performed using descriptive statistics, normality tests, initial ability equivalence tests, Wilcoxon tests, Mann–Whitney tests, and effect size calculations. The results showed a significant difference between the speech writing skills of students who learned using the BERAPI Restitution Strategy based on mindful learning and students who followed conventional learning (p < 0.05). In addition, the effect size calculation showed a very strong influence (r = 0.86), so it can be concluded that the BERAPI strategy is statistically and practically effective. Thus, the application of the BERAPI Restitution Strategy based on mindful learning has been proven to improve speech writing skills while strengthening the internal motivation of eighth-grade junior high school students.   Penelitian ini bertujuan untuk menganalisis efektivitas penerapan Strategi Restitusi Berani Pidato (BERAPI) berbasis mindful learning dalam meningkatkan keterampilan menulis pidato siswa kelas VIII SMP Negeri 2 Kroya pada tahun 2025. Penelitian menggunakan pendekatan kuantitatif dengan rancangan quasi experimental melalui desain nonequivalent control group. Subjek penelitian mencakup seluruh siswa kelas VIII yang berjumlah 256 siswa, dengan penentuan sampel sebanyak 64 siswa yang memiliki rentang nilai awal antara 60 hingga 70. Sampel tersebut dibagi ke dalam dua kelompok, yaitu kelompok eksperimen dan kelompok kontrol, masing-masing berjumlah 32 siswa. Pengumpulan data dilakukan melalui tes menulis pidato yang dinilai menggunakan rubrik penilaian keterampilan menulis pidato yang telah melalui uji validitas dan reliabilitas. Analisis data dilakukan dengan menggunakan statistik deskriptif, uji normalitas, uji kesetaraan kemampuan awal, uji Wilcoxon, uji Mann–Whitney, serta perhitungan effect size. Hasil penelitian menunjukkan adanya perbedaan yang signifikan antara keterampilan menulis pidato siswa yang memperoleh pembelajaran menggunakan Strategi Restitusi BERAPI berbasis mindful learning dan siswa yang mengikuti pembelajaran konvensional (p < 0,05). Selain itu, hasil perhitungan effect size menunjukkan pengaruh yang sangat kuat (r = 0,86), sehingga dapat disimpulkan bahwa strategi BERAPI efektif secara statistik maupun praktis. Dengan demikian, penerapan Strategi Restitusi Berani Pidato (BERAPI) berbasis mindful learning terbukti mampu meningkatkan keterampilan menulis pidato sekaligus memperkuat motivasi internal siswa kelas VIII SMP.